Reengineering sustainability at Universiti Tun Hussein Onn Malaysia (UTHM): travel & transportation - Razally Wahid; Sulaiman Noralfishah; Md. Rohani Munzilah; David Daniel Basil; Mat Radzuan Indera Syahrul; Mohd Junaid Thuwaibah (E3S Web of Conferences, 2018)
Conveniently situated in Parit Raja town which is also known as the “Education Town” in Johor, Universiti Tun Hussien Onn Malaysia (UTHM) is a member of Malaysian Technical University Network (MTUN). In pursuit of turning UTHM as a Green Campus, UTHM has its own ambitious targets for sustainability. It is committed to provide sustainable, efficient, convenient, and safe travel and transport to all students, staffs and visitors. The inception of Sustainable Campus Unit (SCU) in May 2010, showed that UTHM has doubled its green efforts and initiatives to provide sustainable travel and transport in the campus when and where possible. The formation of Strategy in Operation (SIO5): Travel & Transport in the SCU has encouraged active transportation and healthy commuting options in the campus by providing a wealth of innovative green transit options including bus, bicycle, pedestrian, and car. These options indeed will improve the quality of life on campus, strengthens UTHM ties to the neighbouring community, and reduces impacts on the environment as travel and transport system plays an important role on the carbon emission and pollutant level in university. This paper is therefore, trying to discuss some issues, measures and innovative strategies employed at UTHM as an integral part to achieve success in climbing the UI GreenMetric World University Ranking ladder.